Força, armas, leis e milícia em I Primi Scritti Politici, de Maquiavel - Santos, Rodrigo dos (2016)
This dissertation, from I Primi Scritti Politici of Niccolo Machiavelli, presents the so-called "theory of force", called this way by Claude Lefort, founded on the basis of quality training for the Florentine army, whose instrumental force of efficient weapons, well handled, with disciplined men to form an appropriate army for the City of Florence. Regarding the establishment of the theory of force, and in view of all the harm that is incurred to rely on mercenaries in armies mixed in men unpatriotic because they are real betrayers due to the money, Machiavelli proposes the choice before the disjunctive love or force, the use of force for conquest again and preservation of the state. That's why the Italy of his time suffered the hardships of a nation plundered externally, because it was weak in terms of defense and attack. The dream of Machiavelli is to regroup it and the Republic of Florence is to be a pioneer in an organized strategy from the theory of force and a logic that is appropriate, heading to a praxis of freedom. The logic of force is binary, it has a theoretical and strategic way from which Machiavel is becoming clever, and another practical where the weapons, especially the fire ones are indications of real power. The virtuous handling of efficient weapons linked to good laws, mixed with violence when useful, it takes the state to remain in power and defend its condition of freedom. The proof in the dissertation is that the history is instructed to show men that achieve the full harmonization of mezzo uomo e mezzo bestia , essential situation be fixed in the power in the place. And such was the situation of Cesare Borgia and Castruccio Castracani